2022
DOI: 10.1038/s41467-022-32170-x
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical and thermochemical pathways to S2 and polysulfur formation in the atmosphere of Venus

Abstract: Polysulfur species have been proposed to be the unknown near-UV absorber in the atmosphere of Venus. Recent work argues that photolysis of one of the (SO)2 isomers, cis-OSSO, directly yields S2 with a branching ratio of about 10%. If correct, this pathway dominates polysulfur formation by several orders of magnitude, and by addition reactions yields significant quantities of S3, S4, and S8. We report here the results of high-level ab-initio quantum-chemistry computations that demonstrate that S2 is not a produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Moreover, S 8 was detected in Ryugu samples 21 . Sulfur allotropes may also play an important role in providing UV opacity in the Venusian atmosphere 22 , and in Venus-type exoplanets 23 . Density functional theory (DFT) calculations have suggested that among the S N allotropes, octasulfur S 8 is especially stable 24 , with astrochemical models highlighting its relevance in the dynamics of sulfur in the interstellar medium (ISM).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, S 8 was detected in Ryugu samples 21 . Sulfur allotropes may also play an important role in providing UV opacity in the Venusian atmosphere 22 , and in Venus-type exoplanets 23 . Density functional theory (DFT) calculations have suggested that among the S N allotropes, octasulfur S 8 is especially stable 24 , with astrochemical models highlighting its relevance in the dynamics of sulfur in the interstellar medium (ISM).…”
Section: Introductionmentioning
confidence: 99%
“…An essential part of sulfur-rich anoxic chemistry is elemental sulfur. Sulfur dimer (S 2 ) has been observed in various extraterrestrial environments ranging from interstellar clouds to our solar system bodies, such as Venus, Jupiter’s moon Io, , and various comets in our solar system. , …”
Section: Introductionmentioning
confidence: 99%